Efectos del marketing de contenidos y políticas de precios en la eficacia del canal online de la empresa “Hera” - Neira Quesada, María José (2021)
This research begins by explaining, in the first chapter, the complexity of the problem of how to improve the effectiveness of the online channel in the commercialization of the Hera company, which belongs to the personal care products category. It should be noted that the usefulness of the study is not limited to said company, but to all those that start as an enterprise within the online market, especially the organic market. Likewise, the population and the sample calculation are shown. In the second chapter are the objectives of the investigation, which are completely limited to the problem to be solved, as well as the hypotheses. In addition, it is detailed how the research instrument was constructed, which is a survey, and its methodological design is described. In the third chapter, we proceeded to develop a tree diagram that shows the relationship of the researches consulted, the purpose of which is to specify the logic and maintain the thread of the topic. In addition to this, all the theoretical bases considered pertinent for the present study are presented. The research is based on the theories of Supply and Demand, Service and CRM to be able to orient the work in a coherent way to each fact or situation raised. Five components were also included, which were supported by three different authors each in order to explain their definition, their types, and their measurement. Among them are efficiency, the online channel, personal care, the Content Marketing strategy and the discount policy. In chapter four the results of the study are shown and comments are made on each graph in order to interpret and carry out a more in-depth analysis. In the fifth chapter, a solution proposal is made based on the two variables, content marketing and discount policies. This contribution is based on publications through social networks, whose content will have the purpose of increasing the impulse to purchase by end customers. In the sixth chapter, the conclusions of the study are presented based on the results of the instrument and, finally; in the seventh chapter the recommendations for those organic enterprises that wish to improve the effectiveness of their online channel are presented.